Attractiveness of Cattle Dung to Coprophilous Beetles (Coleoptera: Scarabaeoidea and Sphaeridiinae) and Their Segregation During the Initial Stages of the Heterotrophic Succession on a Pasture in Southeast Michigan. Issue 3 (5th June 2020) - Wassmer, Thomas
Abstract: Only a few mostly older studies analyzed the heterotrophic succession of dung beetles in the Midwestern United States. Such studies are needed to track the impacts of the climate crisis on heterotrophic succession and the associated decomposition processes that are central to soil fertility and carbon sequestration. The current study closes this knowledge gap and provides an easy and efficient method to estimate the relative attractiveness of individual dung pads during heterotrophic succession. The dung beetle community of Carpenter Farm in Adrian, Southeast Michigan was sampled for an entire year, including the winter months, using 15 pitfall traps baited with fresh cow manure. Samples were collected after 48 h and again after 72 h exposure time from the bucket content while leaving the bait unhampered. Eighty-four percent of all beetles were caught in the early sample, but only 6 species were missing in the later sample. A cluster analysis based on Pianka's niche overlap identified a statistically higher mean overlap than expected by chance in a null model (model RA3) and divided the species community clearly into three clusters separating most relocators from most dwellers. Despite using a different method, my results confirmed the successional position of most previously described species and added data for several species with poor or unknown successional state. The successional segregation between dwellers and relocators discovered by the cluster analysis was paralleled by a significantly larger body size of relocators across taxonomic groups as compared to dwellers.